The Effect of Various Amounts of Artemia on the Growth and Survival of Post Larvae (PL1-10) Vannamei Shrimp (Litopenaeus vannamei) - Kahfi, Ashabul; Nazlia, Suraiya; Rizwan, T (Jurnal Ilmiah Samudra Akuatika, 2022)
This study aims to determine the effect of various numbers of artemia on the growth and survival of post larvae (1-10) vannamei shrimp (Litopenaeusvannamei). The design used in this study was a non-factorial completely randomized design (CRD) consisting of 3 treatments and 3 repetitions. The dose of artemia (treatment) used was 5-6 individual artemia/pl, 7-8 individual artemia/pl and 9-10 individual artemia/pl. Vannamei shrimp (PL1-PL10) tested were 100 heads per liter of water in a 12L container for 10 days of rearing period. Data were analyzed by using Variety Print Analysis. The results showed that the administration of various amounts of artemia had a significant effect (P<0.005) on survival and growth in absolute length of vannamei shrimp (PL1-PL10). The survival of shrimp that was classified as feasible was at a dose of 7-8 individual artemia/pl as much as 74% pl compared to a dose of 5-6 individual artemia/pl and at a dose of 9-10 individual artemia/pl with survival of 52% pl and 34% pl. While the absolute best length was shown at a dose of 9-10 individuals artemia/pl was at an average level of 5.6 mm, whereas at a dose of 5-6 individuals artemia/pl was at an average level of 5.0 mm and the last at doses 7-8 artemia/pl individuals get an average of 4.8 mm.